Indigenous parents and child welfare: Mistrust, epistemic injustice, and training - Leckey, Robert; Schmieder-Gropen, Raphael; Nnebe, Chukwubuikem; Clouthier, Miriam (Social & Legal Studies, 2022)
The settler state's taking of Indigenous children into care disrupts their communities and continues destructive, assimilationist policies. This article presents the perceptions of lawyers, social workers and judges of how Indigenous parents experience child welfare in Quebec. Our participants characterized those experiences negatively. Barriers of language and culture as well as mistrust impede meaningful participation. Parents experience epistemic injustice, wronged in their capacity as knowers. Mistrust also hampers efforts to include Indigenous workers in the system. Emphasizing state workers’ ignorance of Indigenous family practices and the harms of settler colonialism, participants called for greater training. But critical literature on professional education signals the limits of such training to change institutions. Our findings reinforce the jurisdictional calls away from improving the system towards empowering Indigenous peoples to run services of child welfare. The patterns detected and theoretical resources used are relevant to researchers of other institutions that interact with vulnerable populations.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; australie; canada; care; cours; cycles supérieurs; discipline; droit; enfants autochtones; fem9000; injustice; inégalités; nouvelle-zélande; océanie; politique assimilationniste; périodes historiques; racisme; régions géographiques; santé; science politique et droit; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; états coloniaux

The Impact of COVID-19 on women - United Nations (United Nations Entity for Gender Equality and the Empowerment of Women (UN Women); United Nations Secretariat, 2020)
The year 2020, marking the twenty-fifth anniversary of the Beijing Platform for Action, was intended to be ground-breaking for gender equality. Instead, with the spread of the COVID-19 pandemic, even the limited gains made in the past decades are at risk of being rolled back. The pandemic is deepening pre-existing inequalities, exposing vulnerabilities in social, political and economic systems which are in turn amplifying the impacts of the pandemic. Across every sphere, from health to the economy, security to social protection, the impacts of COVID-19 are exacerbated for women and girls simply by virtue of their sex. This policy brief by the UN Secretary-General explores how women and girls’ lives are changing in the face of COVID-19, and outlines suggested priority measures to accompany both the immediate response and longer-term recovery efforts.
Keywords: 2000 à aujourd'hui; 2020-2029; covid-19; discipline; droit; droits des femmes*; droits humains; pandémie; projet charge mentale; périodes historiques; santé; science politique et droit; thématiques; violences; violences sexistes et sexuelles